Genetic Variation of Six Azadirachta excelsa (Jacks) Jacobs Populations - Abdul Hamid, Hazandy (2009)
The study of the extent and pattern of genetic variation of six populations of Azadirachta excelsa (Jacks) Jacobs, i.e. Manong (Perak), Pokok Sena (Kedah), Sik (Kedah), FRIM (Selangor), Merchang (Terengganu) and Sg. Caru (Pahang) was carried out using starch gel electrophoresis. The analysis on eleven enzyme systems was found to be coded by 25 and 26 loci. The mean of observed heterozygosity ranged from 0.08 to 0.11 and the percentage of proportion of polymorphic loci varied from 61.54% to 73.08%. The extents of genetic identities ranged from 0.81 to 0.98.